Preschoolers' request behaviour and family conflict: The role of family communication and advertising mediation styles. Issue 5 (1st April 2021) - Watkins, Leah; Robertson, Kirsten; Aitken, Rob
Abstract: Managing pre‐school children's purchase requests, and dealing with the conflict that often arises when they are denied, can be a major challenge for parents as they negotiate their children's growing brand exposure and their socialisation as consumers. This study focuses on the communication and mediation styles adopted by parents of pre‐school children to understand the relationship with children's brand exposure, request behaviour and family conflict. The study employed a mixed methods interview approach with 73 parent/child dyads, children participated in one‐on‐one activities with the interviewer, while parents answered closed and open ended survey questions. Results suggest that socio‐oriented communication styles (stressing obedience and parental control), and restricting advertising exposure, may reduce children's brand exposure and frequency of purchase requests. However, a focus on actively managed advertising exposure, and engaging children in open and critical discussion (concept‐oriented communication), are the most important variables in reducing family conflict. The study contributes to our understanding of successful parental consumer socialisation styles by examining outcomes for children in the perceptual stage of consumer development, and the strategies likely to lead to their development as competent consumers. The paper concludes with suggestions for resources to support active mediation and communication styles for families.